A retrospective study of dermal fillers associated necrosis and management - Damianou, Lazaria; Demetriades, Neophytos (Aesthetic Medicine, 2024)
Background: Dermal fillers, including hyaluronic acid, play an important role in aesthetic medicine. The immunological response is minimal, however, proper technique and pathophysiology associated with neutral and non-allergic reactions must be further studied, as adverse events might still occur leading to numerous and severe complications, such as tissue necrosis. Methods: We present a retrospective study with cases of four patients with tissue necrosis, following an aesthetic treatment for either nose correction or lip augmentation. Patients were treated from September 2019 until October 2023 in the Cyprus Facial Surgery office, at the American Medical Center located in Nicosia, Republic of Cyprus. Results: All patients had a severe reaction after 15 minutes to 48 hours following the procedure, but no permanent functional damage was reported after treatment with hyaluronidase and heparin injections. Conclusion: Mastering the injection technique of hyaluronic acid fillers, having thorough knowledge of the materials used, the timing and type of proper treatment is critical for preventing tissue ischemia and mitigating necrosis.